Consumption smoothing and the welfare cost of uncertainty - Yonas Alem; Jonathan Colmer (RWI - Leibniz-Institut für Wirtschaftsforschung, 2018)
Separating the effects of uncertainty from realised events, and identifying the welfare effects of uncertainty, present a number of empirical challenges. Combining individuallevel panel data from rural Ethiopia with high-resolution meteorological data, we introduce a new proxy for income uncertainty - mean-preserving rainfall variability - and estimate that an increase in income uncertainty is associated with reductions in objective consumption and subjective well-being (SWB). Furthermore, 86% of the effect on SWB is attributed to the direct effects of uncertainty, consistent with a model of optimal expectations (Brunnermeier and Parker, 2005). In addition, we find that farmers in more uncertain environments are more resilient to realised rainfall shocks, consistent with a trade-off between optimism about the future and risk-management investments today. These findings suggest that the gains from further consumption smoothing are likely greater than estimates based solely on realised consumption fluctuations.
Keywords: I31; O13; Q12; Q56; 330; income uncertainty; consumption smoothing; subjective well-being; rainfall variability